Organizational Culture in Islamic Boarding Schools: A Psychological Study of Teacher Motivation and Performance - RahmawRachmawatiati, Rachmawati; Hanim , Siti Aisyah; Latifah, Zulty; Indah, Woro (Yayasan Minang Darussalam, 2025)
This study explores the relationship between organizational culture, teacher motivation, and performance in Islamic boarding schools. Organizational culture plays a critical role in shaping the work environment and influencing the motivation of educators. In Islamic boarding schools, where the values of Islamic teachings and community-based learning are emphasized, the organizational culture is expected to significantly impact teachers' performance. The research examines how various dimensions of organizational culture, such as shared values, beliefs, and practices, influence teachers’ motivation and their ability to deliver effective education. Utilizing a psychological approach, the study employs both qualitative and quantitative methods to assess the interplay between these factors. Data were collected through surveys and in-depth interviews with teachers from several Islamic boarding schools. The findings suggest that a supportive organizational culture, characterized by trust, mutual respect, and alignment with Islamic values, enhances teacher motivation and, in turn, improves their teaching performance. The study concludes by highlighting the importance of fostering a positive organizational culture in Islamic educational institutions to enhance teacher satisfaction, professional development, and student outcomes.